Painless scrotal swelling: Ultrasonographical features with pathological correlation - Malai Muttarak (2018)
Scrotal swelling may be due to extratesticular and intratesticular lesions. The majority of extratesticular lesions are benign while the majority of intratesticular lesions are malignant. Ultrasonography (US) is helpful in separating extra- from intratesticular lesions. US can show whether a mass is cystic, solid or complex, and also features such as associated calcifications, epididymal involvement, scrotal skin thickening and colour Doppler flow pattern. Extratesticular lesions include hydrocoele, spermatocoele, varicocoele, epididymal cyst, hernia and tumours of the epididymis and cord structures. Intratesticular lesions include primary tumour, metastases, lymphoma and leukaemia. Tuberculous epididymitis or epididymo-orchitis may also present with painless scrotal swelling. US features of these disease patterns, with pathological correlation, are presented in this pictorial essay.